Improved hybrid stress finite elements with full rotational degrees of freedom for solid and shell analysis - Sim, Catherine Yun Shun. (2009)
The research work presented in this dissertation is on developing hybrid stress finite elements with full rotational degrees of freedom (d.o.f.s) based on an extended Hellinger-Reissner variational principle of linear elastic structural mechanics. Conventional finite elements are based on the minimum potential energy principle using assumed displacement only. On the contrary, hybrid stress elements are multivariate, that is, they employ more than one assumed field variables. In this case, both displacement and stress are most often engaged. This has an edge on conventional finite element method to produce more accurate elements. In comparison, conventional finite elements are prone to membrane/shear locking, sensitive to aspect ratio, have poor stress predictions and are susceptible to mesh distortion.